Are reporting and investigation of rape cases victim friendly? Responses of the police from a cross-sectional study conducted in three states of eastern India - Swetapadma, Sonali (International review of victimology, 2024)
The police are the first stakeholders within the criminal justice system responding to the offence of rape. Some specific laws have been enacted in India with the aim of incorporating a victim-friendly approach during the stages of reporting and investigation of rape cases by the police. This paper presents the results from the responses of the police from a cross-sectional study conducted in the states of Odisha (OD), Jharkhand (JH), and West Bengal (WB) in eastern India to see their approaches to the implementation of the victim-friendly provisions of the law at such specific stages. It presents the police perceptions on compliance with laws pertaining to reporting, registration and investigation of rape cases in the three selected states and the corresponding state-wise differences in police attitudes. The findings show that there is more non-compliance and there are differences in the degrees of compliance or non-compliance in the three states.